2004
DOI: 10.1093/ps/83.8.1287
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of maize containing known levels of fumonisin B1 during force-feeding of ducks

Abstract: The toxicity of maize containing known doses of fumonisin B1 (FB1) was investigated in mallard ducks during force-feeding. Seventy-five ducks at 12 wk of age were randomly divided into 3 groups of 25, and received control maize, naturally contaminated maize containing 20 mg/kg of FB1, or a mixture of control and contaminated maize (50/50, vol/vol). Force-feeding was performed during 12 d that correspond to a final average feed intake of approximately 10 kg of maize per duck. At the end of the study, 8% mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
2
13
1
Order By: Relevance
“…Olayemi et al (2002) reported that, in the 306 Nigerian duck, plasma concentrations of ALT and AST were lower in younger ducks than in 307 adults. While overall ALT levels were similar in the Pekin ducks from our study and those 308 from the other papers (Tardieu et al, 2004;Tran et al, 2005), the LDH level was much 309 lower. In contrast, activities of ALT and AST in our study were lower and activity of LDH 310 was higher level than the values for adult mule ducks given by Samour (2000).…”
Section: Discussion 224supporting
confidence: 74%
See 1 more Smart Citation
“…Olayemi et al (2002) reported that, in the 306 Nigerian duck, plasma concentrations of ALT and AST were lower in younger ducks than in 307 adults. While overall ALT levels were similar in the Pekin ducks from our study and those 308 from the other papers (Tardieu et al, 2004;Tran et al, 2005), the LDH level was much 309 lower. In contrast, activities of ALT and AST in our study were lower and activity of LDH 310 was higher level than the values for adult mule ducks given by Samour (2000).…”
Section: Discussion 224supporting
confidence: 74%
“…Generally, reported 299 blood concentrations for ducks appear difficult to compare because they show a large 300 variation between and within studies, the reasons for which are only partly known. Mule 301 ducks had significantly increased blood plasma concentrations of LDH and ALT after a 12-d 302 force-feeding period (Tardieu et al, 2004) (Tran et al, 2005). Laying Tsaiya ducks developed higher blood serum levels of LDH and AST when exposed to dietary supplements of 3-nitro-4hydroxyphenylarsonic acid (Chen et al, 2000).…”
Section: Discussion 224mentioning
confidence: 99%
“…In the same way, maize can represent 99% of the diet in duck and geese during force feeding. Because of the high amount of diet provided, this production is highly exposed to fumonisins and risk of toxicity [151]. …”
Section: Pig and Poultry Exposurementioning
confidence: 99%
“…In horses, FB 1 mainly affects the brain inducing leukoencephalomalacia, while in pigs the heart and lungs are the most important target organs of FB 1 , causing pulmonary edema [ 14 ]. Poultry are often considered to be quite resistant toward the deleterious effects of FBs, although important differences are observed depending on the age [ 19 ] and species [ 20 , 21 , 22 , 23 , 24 ]. Increased mortality due to FB 1 has only been demonstrated in broiler chicks during the first three days of life (≥125 mg/kg feed) [ 19 ] and in growing ducks of 12–14 weeks old (20 mg/kg feed) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poultry are often considered to be quite resistant toward the deleterious effects of FBs, although important differences are observed depending on the age [ 19 ] and species [ 20 , 21 , 22 , 23 , 24 ]. Increased mortality due to FB 1 has only been demonstrated in broiler chicks during the first three days of life (≥125 mg/kg feed) [ 19 ] and in growing ducks of 12–14 weeks old (20 mg/kg feed) [ 22 ]. No mortality has been recorded in laying hens, turkeys or older broiler chickens fed high doses of FB 1 (≥200 mg/kg feed) for several weeks [ 20 , 21 , 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%